2018
DOI: 10.1186/s40104-018-0243-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lactobacillus acidophilus on the growth performance and intestinal health of broilers challenged with Clostridium perfringens

Abstract: BackgroundClostridium perfringens is the main etiological agent of necrotic enteritis. Lactobacilli show beneficial effects on intestinal health in infectious disease, but the protective functions of lactobacilli in C. perfringens-infected chickens are scarcely described. This study examined the effects of Lactobacillus acidophilus (L. acidophilus) on the growth performance and intestinal health of broiler chickens challenged with Clostridium perfringens (C. perfringens) over a 28-day period. Using a 2 × 2 fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
109
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(126 citation statements)
references
References 40 publications
16
109
0
1
Order By: Relevance
“…It was shown that broiler challenged with C. perfringens resulted in decrease of claudin‐1 and occludin gene expression and however disrupted the TJs between the epithelial cells Du et al (). Similarly, Li et al () discovered that C. perfringens challenged chickens decreased occludin mRNA expression in the jejunum. In this study, the mRNA relative expression in BL‐fed group showed higher expression of claudin‐1 in the duodenum (d7 and d21) and jejunum (d21) and ZO‐1 on the ileum (d21).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It was shown that broiler challenged with C. perfringens resulted in decrease of claudin‐1 and occludin gene expression and however disrupted the TJs between the epithelial cells Du et al (). Similarly, Li et al () discovered that C. perfringens challenged chickens decreased occludin mRNA expression in the jejunum. In this study, the mRNA relative expression in BL‐fed group showed higher expression of claudin‐1 in the duodenum (d7 and d21) and jejunum (d21) and ZO‐1 on the ileum (d21).…”
Section: Discussionmentioning
confidence: 89%
“…However, in another related study, B. subtilis showed positive effect on histomorphology and gut integrity of villi against C. perfringens ‐induced NE in broiler birds (Abudabos, Alyemni, & Almarshad, ; Jayaraman et al, ). Additionally, in a study with Lactobacillus acidophilus supplementation in broiler diet reduced the mortality rates and increased jejunal crypt depth, which support intestinal renewal and infection recovery Li, Wang, Dan, and Gao (). Thus, the frequency for higher intestinal villus in duodenum, jejunum and ileum and crypt depth in the challenged group could be attributed to the dose of the C. perfringens , challenge method, and length of time for the probiotics and AGP administrations.…”
Section: Discussionmentioning
confidence: 95%
“…After chickens were infected with CP or on the subclinical infection of NE, the small intestine was damaged [12,23]. The intestinal injury may cause CP to reach the bile duct and portal vein blood flow [24].…”
Section: Discussionmentioning
confidence: 99%
“…in humans. Clostridium perfringens is the main etiological agent of necrotic enteritis in broilers (Li et al, 2018). The Clostridia decreased in broilers given feed supplemented with TFEO at 100, 200 and 400 mg/kg compared with the control group at 21 days, and significantly decreased at 42 days, which shows that TFEO can inhibit the Clostridia in broiler cecum, and thereby prevent diseases such as necrotic enteritis.…”
Section: Tfeo and Intestinal Microfloramentioning
confidence: 89%